ASN dalam Pendidikan Tinggi: Transformasi dan Akreditasi - Anwar Sanusi; Masduki Asbari; Ardi Ardiansah (AGUSPATI RESEARCH INSTITUTA, 2023)
The purpose of establishing the competence of the Department is not with a prescription determined by national standards but with a quality framework determined by national standards of higher education, to realize the standards developed by universities referring to their pramwork, internal quality assurance becomes not detailed in this regulation and therefore we provide flexibility of academic autonomy to universities by utilizing Creation and Innovation which is widely opened in accordance with Candy-53, Year 2023. External quality assurance system For 3 years It has transformed the Accreditation System based on the Independent Accreditation institution in accordance with the provisions of the Constitution 12-2012 Using an Independent System Developed By (LAM). In this study report using a descriptive qualitative method by taking notes because the source of the data obtained by listening to the oral narration from the Yotube channel of Dtjen Dktiristek entitled